Clinical presentation of maternal death with COVID-19 in rural tertiary care center: A retrospective-descriptive Study - Devita Kurniawati, -
Abstract Background: Maternal with to COVID-19 is a new maternal emergency issue leading to maternal morbidity and mortality. In Indonesia, the number of cases of maternal mortality with COVID-19 began to increase. This study aims to determine the characteristic of maternal deaths due to COVID-19 in a tertiary care center in Indonesia.